Ketidakstabilan Kawasan dan Peningkatan Peran Amerika Serikat di Asia Timur Pasca Perang Dingin - Ni Luh Bayu Purwa Eka Payani (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2016)
After The Cold War ended, US started to dominate the whole world with its ideology and other influences. East Asia is one of the battlefields between Liberal and Communist Ideology, which is until now; the tense is still felt among the countries. The uncertain and unstable situation made US as a victor and close alliance to Japan and South Korea to intervene in setting security map in the region. Instability emerges when the countries within region try to build their military up (military buildup) to offset one another, internal conflicts between countries, and nuclear provocation by North Korea, which is not only threatening region but also the US existence in the region. To encounter these challenges, US needs to increase its role in settling instability in East Asia.